The Effect of Parent Support and Self Regulated Learning on Learning Motivation on Students in SDIT Insan Utama - Tri Widayati; Akif Khilmiyah; Aris Fauzan (Ridwan Institute, 2022)
This study aims to determine how far the influence of parental support and self-regulated learning on students' learning motivation. This research is a research model of hypothesis testing (hypothesis testing study) with a quantitative approach. Data were collected using a questionnaire/questionnaire in the form of a Likert scale on parental support, self-regulated learning and learning motivation. The population was taken from all students of SDIT Insan Utama Yogyakarta with a simple random sampling technique with a sample of 152 students. Data analysis consisted of validity and instrument reliability tests, normality tests, linearity tests, hypothesis tests and correlation tests. The results of this study indicate that 1) Parental support has a significant effect on student learning motivation by 7.7% and has a moderate correlation with the Pearson Correlation value of 0.278; 2) Learning motivation has an effect on student achievement by 31.8% and is perfectly correlated with the Pearson Correlation score of 0.564; 3) Parental support and self-regulated learning together have an effect on student learning motivation by 32.9% with a significance value of 0.000. 4) The indicators of parental support variable are the provision of accommodation, motivation, appreciation, regulatory support, comfort, opportunities for activities, discussions and joint activities. Indicators of self-regulated learning variable are learning process control, setting learning goals, setting time and school assignments, motivation, planning, evaluating, implementing plans and asking for help if needed. The indicators of learning motivation variable include having an effort to learn, being able to maintain perseverance in learning and focusing on achieving learning goals.